Obtenção de etanol a partir da fermentação do permeado de soro de queijo utilizando a levedura Saccharomyces cerevisae - Vignaga, Indiara Ruthelli Lunardi (2017)
The Cheese Whey Permeate is a byproduct of the dairy industry with potential for several applications in fermentative biotechnological processes, since it is rich in lactose and mineral salts. This paper aims to obtain ethanol with the aid of S. cerevisae, using liquid cheese whey permeate as medium. The permeate was first characterized and then submited to a enzymatic hydrolysis using the -galactosidade enzyme 6000 U under a concentration of 1,05g/L, a 200 rpm stirring, under 37,5ºC during 120 minutes in a bioreactor. Later, a kinetic evaluation was conducted through a fermentation in shaker, under the temperature of 30ºC, initial medium pH of 5,00, with no extra supplementation and no stirring during 24h. The second step was to verify how temperature, pH and supplementation affect the ethanol production. A central composite experimental design and response surface methodology were applied. Using the best results obtained through the experimental design, a second enzymatic evaluation was conducted, this time in a bioreactor, allowing upsize. The cheese whey permeate hydrolysis resulted in conversion rates of over 92%. In the preliminary kinetics the yield (Y p/s) was 0,27 (g/g) and the productivity was 1,65 (g/L.h). The experimental design displayed that the “temperature” have a level of significance of 95% in the ethanol production. Among all the evaluated conditions, the highest value of obtained ethanol was 22,42 g/L, when the fermentative medium was kept under 30ºC, pH 6,30 and supplemented with 2 g/L of yeast extract and 1 g/L of peptone. In the bioreactor fermentative experiment, the value of obtained ethanol was 22,45 g/L, a rate of 1,70 g/L.h and a yield (Y p/s) of 0,47 g/g. A 30,15% reduction in the DQO rate was achieved. Therefore, this paper presented that the cheese whey permeate is a byproduct of high potential of being applied in ethanol production using yeast. An alternative to the use of fossil fuels and allowing a reduction in the organic load of the original product, which is a parameter linked to the reduction of the environmental impact as well as to the reduction of costs related to wastewater treatment.